LEADERSHIP AS A SPECIAL KIND OF IMPACT ON EMPLOYESS - GAJDA, Joanna (Trends in education, 2013)
Enterprise operating in the present environment, to keep up with the global trends in economic development need an effective leadership. Leadership is required to implement in constructive changes, which ultimately result in maintaining consistency between the organization and the environment. This paper presents an approach to leadership, especially the role of charismatic leadership. Moreover charismatic theories determine how situational factors interact, so that one can determine the appropriate leadership behavior. The concept of charismatic leadership assumes that it is required a particular personality feature, such as charisma, which is an important factor of the efficient impact on the other employees.
Keywords: leadership; relationships; charisma; decisions; participation; effectiveness